Peran Pengetahuan Perawat terhadap Penerapan Patient Safety Pasca Operasi: Studi Cross-Sectional - Nurul Jannah; Arif Budiwibowo; Anas Kiki Anugrah; Mukhlis Mukhlis; Dian Apri Nelyanti; Mei Sintia (ARTERI : Jurnal Ilmu Kesehatan, 2026)
Approximately 28.3% of patient safety incidents in Indonesia are committed by nurses. Patient safety incidents (PSIs) increased significantly from 289 incidents in 2015 to 668 incidents in 2016, reaching 1,647 incidents in 2017. This increase highlights the urgency of improving patient safety practices, especially in the post-operative phase, which is a critical period for patients who are vulnerable to infection, medication errors, and procedural negligence. Nurses' knowledge of patient safety is crucial in preventing such undesirable events. Objective: This study aims to determine the relationship between nurses' knowledge and the implementation of postoperative patient safety in the operating rooms of Bima City Hospital in 2025. Methods: This study used a quantitative design with a cross-sectional approach. The study population consisted of 36 nurses, with data collection using a validated questionnaire and data analysis using the Spearman Rho test (α = 0.05). Results: The results showed that most respondents had sufficient knowledge about patient safety (41.7%), while the implementation of patient safety after surgery was in the good category (66.7%). The Spearman correlation coefficient showed a value of 0.49 with a p-value of 0.002, indicating a moderate positive relationship between nurses' knowledge and the implementation of patient safety after surgery. Conclusion: There is a significant relationship between nurses' knowledge and the implementation of patient safety, indicating that the higher the nurses' knowledge, the better the implementation of patient safety. It is recommended that hospitals improve training and socialization of patient safety to strengthen nurses' competencies.